DINAMIKA BUDAYA ORGEN TUNGGAL DALAM MASYARAKAT NAGARI LUBUK ALUNG KECAMATAN LUBUK ALUNG - Hergiansyah Hergi; Syamsir; M. Hafiz Al Habsy; Tasya Aulia Oktavia; Putri Anggraini; Riri Puspita; Siti Hamidah (PROSIDING SEMINAR NASIONAL PENDIDIKAN, BAHASA, SASTRA, SENI, DAN BUDAYA, 2023)
Besides being rich in natural resources, Indonesia is also rich in musical diversity, such as traditional music that is unique to Indonesia, namely tambourine, salung, angklung, gamelan and so on. In addition to traditional music, there is also international music, namely pop, jazz, rock and so on. The single organ or keyboard at the present time is already popular in society, so there are many enthusiasts and it is widely used in many areas in West Sumatra, especially in Nagari Lubuk Alung. In accordance with Padang Pariaman Regent Regulation (Perbup) Number 13 of 2016 concerning Management of Single Organs, this is a form of policy that regulates solo organ performances so that they do not conflict with general values and norms. This type of research is semi-qualitative research. This type of research is a descriptive approach. The descriptive method is finding facts with the correct interpretation. Descriptive study of the problems and procedures of society that are applied in society and in certain situations, including human relations, actions, attitudes, perspectives and processes that take place and the consequences of phenomena. The location of the research was in Nagari Lubuk Alung, Lubuk Alung District, Padang Pariaman Regency. Data collection techniques used in this study were interviews and observations.